The isolation of glycosides from the leaves of Lagerstroemia speciosa (Linne) Person (Banaba) - Javier, Clarissa R.
Leaves of Lagerstroemia speciosa (Linne) Person was coarsely comminuted, dried and percolated to exhaustion using 95% ethanol. The concentrated extract obtained was used for thin-layer chromatography (TLC) to determine what solvent would best elute the active constituent. Extraction process for glycosides is used to isolate, crudely, the glycoside present in the leaves.